E-Learning Based Web Programming Course in the COVID 19 Pandemic Time - Novaliendry, Dony; Huda, Asrul; Cuhanazriansyah, Muhammad Rinov; Sani, Hesty Kumala; Hendra, Herisvan; Karnando, Joni (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The learning process in the STKIP PGRI West Sumatra Informatics Education Study Program still uses conventional learning methods, namely through face-to-face contact between lecturers and students in the class. The traditional learning method currently taking place has limitations that can hinder the learning process, such as limited time and space to interact with each other, especially during the Covid-19 pandemic. With these conditions, the online learning process is an alternative to support learning in its current state, with technological developments that can simplify the learning process and make the time more flexible and support the learning process anywhere, anytime, and anyone. An electronic learning system (E-Learning) was created from these conditions, which is expected to be an alternative solution for online learning to overcome the STKIP PGRI West Sumatra Informatics Education Study Program's limitations, especially in introductory web programming courses. E-learning is designed using the System Development Life Cycle (SDLC) method supported by the PHP programming language and implementing the Laravel Framework. The learning process using E-learning is designed using localhost as the central server. This study's results resulted in an E-learning application built based on the analysis and design recommended by the STKIP PGRI West Sumatra informatics education study program. With this application, it is hoped that it can simplify the online learning process, especially in existing introductory web programming courses.